IL4Rα and ADAM33 as genetic markers in asthma exacerbations and type‐2 inflammatory endotype. Issue 8 (21st April 2017) - Sunadome, H.; Matsumoto, H.; Petrova, G.; Kanemitsu, Y.; Tohda, Y.; Horiguchi, T.; Kita, H.; Kuwabara, K.; Tomii, K.; Otsuka, K.; Fujimura, M.; Ohkura, N.; et al.
Summary: Background: Genetic markers of susceptibility to asthma exacerbations in adults remain unclear. Objective: To identify genetic markers of asthma exacerbations, particularly in patients with type‐2 inflammatory endotype. Methods: In this observational study of patients enrolled in the Kinki Hokuriku Airway disease Conference multicenter study, frequency of exacerbations requiring systemic corticosteroids during 2 years after enrolment and associated risk factors was determined. For genetic marker analysis, interleukin‐4 receptor α ( IL4RA ) rs8832 and a disintegrin and metalloprotease 33 ( ADAM33 ) S_2 (rs528557), T_1 (rs2280091), T_2 (rs2280090), and V_4 (rs2787094) variants were included. Elevated serum periostin levels at enrolment (≥95 ng/mL, defined as type‐2 inflammatory endotype) were considered in the analysis. Results: Among 217 patients who were successfully followed up for 2 years after enrolment, 60 patients showed at least one asthma exacerbation during the 2 years. Airflow limitation (%FEV1 <80%) and recent exacerbations but not genetic variants were identified as risk markers of exacerbations. A total of 27 patients showed type‐2 inflammatory endotype (serum periostin ≥95 ng/mL at enrolment) and subsequent exacerbations; risk factors in these patients were airflow limitation (odds ratio, 6.51; 95% confidence interval (CI): 2.37–18.6; P =.0003), GG genotype of IL4RA rs8832 (odds ratio, 4.01; 95% CI: 1.47–11.0; P =.007), and A allele of ADAM33 T_2 (odds ratio, 2.81; 95% CI: 1.05–7.67; P =.04) by multivariate analysis. In addition, GG genotype of IL4RA rs8832 was associated with type‐2 endotype, whereas A allele of ADAM33 T_2 was associated with mixed type of eosinophilic/type‐2 and neutrophilic inflammations. Conclusions and Clinical Relevance: IL4RA and ADAM33 variants may be risk markers of asthma exacerbations in type‐2 inflammatory endotype. Precise endotyping may facilitate the identification of genetic risk markers of asthma exacerbations.